Effects of Ventilator-Associated Pneumonia Among Saudian’s Critically Ill Patients, Systemic Review - Al-Gethami, Ebtisam Hanshool Mauof (British Journal of Healthcare and Medical Research, 2022)
Introduction: Mechanically ventilated patients are vulnerable to infectious diseases, such as ventilator-associated pneumonia (VAP), due to the breach of normal defence mechanisms and relative immune paralysis during ventilation. This study aimed to determine the risk factors for developing VAP among ventilated patients, as well as the incidence and effects of VAP in Saudi Arabia. Methods: A systematic review design was used. The included studies were published after 2015 in the English language and relevant to the topic of concern. Results: Eleven articles were selected for inclusion in the study. The incidence of VAP in Saudi Arabia was low during the study period. Risk factors for developing VAP included a lack of adequate nurse training, a failure to closely supervise ventilated patients, chest and rib injuries, reintubation, the supine position, and old age. VAP led to increased rates of sepsis, multi-drug-resistant infections, mortality, and longer ICU and hospital stays, as well as developing complications Conclusion: The use of the VAP prevention and treatment bundle and other strategies reduced the risk of ventilated patients developing VAP.